2012
DOI: 10.3928/01477447-20120919-26
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Neglected Posterior Fracture–Dislocation of the Shoulders

Abstract: Posterior dislocation of the shoulder is an uncommon injury. Diagnosis is difficult and often missed. Once diagnosed, management must be individualized depending on the amount of the defect of the humeral head and the time from injury. This article presents a case of a 40-year-old man with a 4-month history of bilateral locked posterior fracture-dislocation of the shoulders after a grand mal seizure. Imaging showed loss of the glenohumeral joint lines congruency, reverse Hill-Sachs lesions, and articular defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
(29 reference statements)
2
10
0
Order By: Relevance
“…[51] 2012 1 45 M Seizures Bil 3 AP Kokkalis et al. [55] 2012 1 40 M Seizures Bil 4 AP AP = anteroposterior radiograph; F = female; M = male. …”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
“…[51] 2012 1 45 M Seizures Bil 3 AP Kokkalis et al. [55] 2012 1 40 M Seizures Bil 4 AP AP = anteroposterior radiograph; F = female; M = male. …”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
“…Although the literature contains many case reports dealing with the neglected posterior shoulder dislocation, 9 , 11 , 14 , 15 , 16 only a limited number of case series are available that report on the transfer of the lesser tuberosity. 1 , 12 , 17 In the study by Hawkins et al, satisfactory outcomes were reported in 4 patients with a mean follow-up of 5.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft reconstruction is preferable to arthroplasty in larger defects in relatively younger patients (Table I). [1,[7][8][9][10][11][12][13][14] For patients who have good bone quality of the residual head and an absence of relevant osteoarthrosis, reconstruction with an allograft represents a viable alternative to hemiarthroplasty or total joint arthroplasty for carefully selected larger defects. However, our follow-up time was too short to recommend whether avascular necrosis or graft collapse would develop, since posterior bilateral dislocation was usually experienced by middle-aged active males.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we suggest that hemior total arthroplasty should be reserved the final treatment of choice. [11] Ivkovic et al [2] Gerber et al [12] Kokkalis et al [9] Martínez et al [14] Torrens et al [1] Aparicio et al [6] Hawkins et al [7] Number of cases Clinical and radiological results, excellent.…”
Section: Discussionmentioning
confidence: 99%